Bacterial community composition and diversity under increasing loading rates in reed wetland for sludge treatment - Tahra Al-Rashdi; Daniel Menezes Blackburn; Mushtaque Ahmed (Elsevier, 2024)
Efficient and sustainable sludge management is a significant environmental and health challenge. Sludge-treatment reed beds (STRBs) are widely recognized as a cost-effective, highly efficient, and environmentally friendly solution for sludge treatment and dewatering. This study investigated the bacterial community composition and diversity in pilot-scale STRBs operating at different sludge loading rates (75, 100, and 125 ​kg ​m2 year−1). 16S rRNA V4 DNA sequencing was used to assess the diversity of the bacterial communities within the sludge samples. The relative abundance of prokaryotic taxa was affected by all treatments. As the sludge loads increased, the Shannon entropy and evenness diversity also increased for the STRBs and unplanted beds. Interestingly, the presence of reeds resulted in significantly lower Shannon and evenness indices than unplanted beds, regardless of the sludge. Additionally, the correlation network analysis revealed distinct microbial clusters with distinct responses to reeds and sludge loads. Principal component analysis evidenced an association between cluster 5 and organic matter decomposition, primarily at higher sludge doses, while clusters 4 and 6 were related to sludge decomposition at lower doses. Additionally, cluster 4 was associated with nutrient removal. The formation of distinct microbial niches was linked to sludge stabilization and nutrient removal and was influenced by both sludge loading rates and the presence of reeds. Future research can leverage these findings to innovate pollutant removal and ecosystem services for sludge treatment, thus advancing sustainable sludge management and environmental preservation.